ACTIVE AND PASSIVE CRITERIA OF VIOLATION OF HUMAN RIGHTS - Oleshchenko, Veronika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to investigate the prerequisites of violations in the field of human rights and to propose their classification in order to create more effective mechanisms for the protection and enforcement of human rights, as well as to reduce the level of violations in this field. The methodological basis of the research consists of general methods of thinking, functional, systemic, structural and synergistic methods. Results: it is proposed to divide violations in the field of human rights according to the criteria of action into active and passive, on the basis of which to determine the prerequisites that cause violations in the specified field. The active criterion of violation of human rights is seen in an external active action or inaction, which is aimed at the intentional violation or obstruction of the exercise of rights by another person, the passive criterion involves the violation of human rights in the absence of available mechanisms and means for their implementation. Discussion: in the issue of the observance and enforcement of human rights, considerable attention is paid to enforcement mechanisms, but the prerequisites for the violation of these rights are also worthy of attention. It is possible to look at the problem of insufficient provision of human rights through the prism of the prerequisites for their violation, thereby solving the issue not at the stage of already violated rights, but preventing such actions. Ensuring human rights is a rather complex and complex issue. Therefore, in this direction, various institutions cooperate in different directions, depending on the goals and methods. When solving the issue of violation of human rights, it is proposed to apply the criterion to determine the reasons that are the basis of the violation of human rights. Based on the analysis of the results of monitoring data among the most violated human rights, the author proposes to divide these violations into active and passive violations according to the criterion of action. Under active violation of rights, it is proposed to understand the deprivation of a person’s opportunity to exercise his rights due to an external illegal act or inaction aimed at hindering the possibility or altogether depriving him of this opportunity to exercise his rights. The passive violation of rights should be understood as the impossibility (or the presence of an obstacle to the free exercise) of a person’s rights due to the lack of mechanisms, methods, and means of ensuring them. Determining the prerequisites for the violation of human rights using criteria for active and passive actions will make it possible to either reduce the number of such cases or eliminate them altogether. That is, the idea of dividing violations of human rights according to active and passive criteria, in a general sense, aims to prevent such violations, eliminate or reduce the grounds for their commission. The application of the specified criteria is also appropriate in the transformation of mechanisms for ensuring human rights, when the volume of the problem is too large and burdensome for the state, it is likely that the prevention of violations in the field of human rights is one of the solutions to this problem.